2022
DOI: 10.1038/s41467-022-31859-3
|View full text |Cite|
|
Sign up to set email alerts
|

A nanoengineered topical transmucosal cisplatin delivery system induces anti-tumor response in animal models and patients with oral cancer

Abstract: Despite therapeutic advancements, oral cavity squamous cell carcinoma (OCSCC) remains a difficult disease to treat. Systemic platinum-based chemotherapy often leads to dose-limiting toxicity (DLT), affecting quality of life. PRV111 is a nanotechnology-based system for local delivery of cisplatin loaded chitosan particles, that penetrate tumor tissue and lymphatic channels while avoiding systemic circulation and toxicity. Here we evaluate PRV111 using animal models of oral cancer, followed by a clinical trial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 96 publications
0
17
0
1
Order By: Relevance
“…Moreover, all secondary endpoints (cisplatin biodistribution, loco-regional control, and technical success) were reached. Finally, no drug-related serious adverse events or locoregional recurrences were reported in 6 months [ 55 ]. In conclusion, the integration of PRV111 with current standard of care may have positive effects on the health outcomes and survival of patients with OCSCC.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, all secondary endpoints (cisplatin biodistribution, loco-regional control, and technical success) were reached. Finally, no drug-related serious adverse events or locoregional recurrences were reported in 6 months [ 55 ]. In conclusion, the integration of PRV111 with current standard of care may have positive effects on the health outcomes and survival of patients with OCSCC.…”
Section: Resultsmentioning
confidence: 99%
“…CIS has great potential as a new type of cancer therapy ( Squillace et al, 2022 ). Studies have shown that its effective anticancer activity was due to cuproptosis caused by elevated levels of reactive oxygen species ( Goldberg et al, 2022 ). We have previously performed experiments with isolated mitochondria without copper, thus hindering the identification of the essential role of this ion.…”
Section: Discussionmentioning
confidence: 99%
“…OSCC is the most prevalent type of head and neck cancer leading to substantial morbidity and mortality. 1 Conventional treatment types such as surgical resection, radiotherapy, and chemotherapy, [2][3][4] can effectively treat early-stage tumors but are less effective for advanced and metastatic cancers. 5 In recent years, cancer immunotherapy has emerged as a new type of treatment for primary tumors, as activated immune cells can recognize and eradicate residual cancer cells, thereby reducing tumor metastasis and recurrence.…”
Section: Introductionmentioning
confidence: 99%